Key Role of Left Atrial Appendage during Redo Ablation in a Case of Long-Standing Persistent Atrial Fibrillation - Shaohui Wu; Guangchen Zou; Xu Liu; Weifeng Jiang; Mu Qin; Daoliang Zhang (Case Reports in Cardiology)
Extrapulmonary vein focal sources have been recognized as the source of atrial fibrillation in some cases, and empiric electric isolation of the left atrial appendage has been proposed for long-standing persistent atrial fibrillation by some. Here, we present a case of redo ablation of long-standing persistent atrial fibrillation in which the left atrial appendage played a key role in maintaining AF during ablation, and atrial fibrillation was terminated by electrical isolation of the LAA. During the ablation, a rare phenomenon of half of the atria in atrial fibrillation while the other half of the atria in atrial flutter was seen.